Evaluation of a multiplex real-time PCR targeting the β-tubulin gene for the detection and differentiation of Sporothrix schenckii and Sporothrix brasiliensis - Luisa F. López; Lalitha Gade; Anastasia P. Litvintseva; D. Joseph Sexton (Microbiology Spectrum)
ABSTRACT Sporothrix sp. is a thermally dimorphic genus of fungi known to cause subacute or chronic subcutaneous lesions in humans and animals and is the cause of increasing public health concern due to spread of feline-associated cases. Here, we adapted and evaluated a recently described real-time PCR assay targeting the β-tubulin gene to rapidly detect and differentiate two related species, S. schenckii and S. brasiliensis. The assay was tested with 55 S. brasiliensis, 19 S. schenckii, and 85 isolates from other clinically relevant fungi, and showed 100% concordance with reference identification methods. The assay showed high analytical sensitivity with a limit of detection of 1 pg of DNA per microliter of sample for both targets. The assay was further evaluated with 11 fresh and 17 formalin-fixed, paraffin-embedded (FFPE) tissues. This multiplex real-time PCR assay successfully detected the DNA from both S. brasiliensis and S. schenckii isolates as well as S. schenckii from fresh and FFPE tissues. Our results demonstrate this assay performs well and could be a helpful molecular tool to support rapid species identification in cultures and primary specimens.IMPORTANCEHaving available molecular tools to identify and differentiate closely related species will allow clinical, veterinarians, and public health labs to provide diagnostic results with accuracy and short turnaround time for the routine and outbreak response activities.